IMPLEMENTASI UNDANG-UNDANG NOMOR 19 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PETANI STUDI KASUS DI DESA BENDILWUNGU KECAMATAN SUMBERGEMPOL KABUPATEN TULUNGAGUNG - Muhammad Syarifudin Haris; Mohammad Hasib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia's agricultural sector contributes approximately 13.14% to the national Gross Domestic Product (GDP); however, farmers' welfare remains considerably low, as indicated by a Farmers' Terms of Trade (NTP) index frequently below 100. This condition prompted the enactment of Law Number 19 of 2013 on the Protection and Empowerment of Farmers as a strategic legal instrument. Despite being in force for over a decade, its implementation at the village level remains academically underexamined, particularly in rural East Java, including Bendilwungu Village, Sumbergempol District, Tulungagung Regency. The gap between the normative substance of the law and its actual field implementation constitutes the primary urgency of this study. This research aims to analyze the implementation of Law No. 19 of 2013 and identify its supporting and inhibiting factors in Bendilwungu Village. A descriptive qualitative method with a case study approach was employed. Data were gathered through in-depth interviews, observation, and documentation involving village officials, agricultural extension workers, and local farmers. Findings reveal that implementation remains suboptimal, characterized by limited farmer access to subsidized production inputs, weak farmer group institutional capacity, and insufficient regulation-based empowerment programs. Primary inhibiting factors include constrained regional budgets, low human resource capacity, and unsynchronized cross-sectoral coordination. This study concludes that strengthened coordination among village governments, agricultural agencies, and relevant institutions is essential to substantively and sustainably realize farmer protection and empowerment.